'Organisation of contraceptive care' and attitudes among healthcare providers in two Swedish cities with different socio-demographic profiles. (June 2015) - Palmquist, Moa; Brynhildsen, Jan; Falk, Gabriella
Abstract: Objective To compare contraceptive services provided by family planning clinics in Linköping and Norrköping in Östergötland County, Sweden. The two cities are of similar size but have different socio-demographic profiles. The abortion rate in Linköping (15.3 per 1000) is substantially lower than in Norrköping (21.1 per 1000). Methods The study was performed in two steps. First, the clinics providing contraceptive services in the two cities were studied using ten pre-defined quality indicators. Thereafter, 11 healthcare providers were interviewed: six in Linköping and five in Norrköping. The interviews were analysed using qualitative content analysis. Results No differences were found in the organisation of contraceptive care in the two cities. Neither city met the criteria for five of the ten quality indicators. The analysis of the interviews generated four themes: 'Guidelines and electronic record template', 'Criteria for good contraceptive counselling', 'Availability of contraception', and 'Sexual health'. The interviews revealed that the clinical leadership in Norrköping was insufficient. Conclusion Clinics in the two cities are organised in the same way so that differences in abortion rates cannot be related to differences in organisation. The reasons for the differences in abortion rates in the two cities have yet to be determined. Chinese Abstract 摘要 目的 比较瑞典östergötland郡的Linköping和Norröping 这两个城市计划生育诊所提供的避孕服务的质量。这两个城市大小规模相似，但是社会-人口学特征不同。在Linköping流产率为15.3‰，明显低于Norröping 的21.1‰的流产率。本研究调查这两个城市的流产率不同是否是因为他们提供的计划生育避孕服务质量不同造成的。 方法 这个研究分两步进行。第一步，应用避孕服务质量的十项质控标准来对这两个城市提供避孕服务进行判定。然后，我们对11位从业人员进行访谈，其中6名是Linköping的，5名是Norröping的。对访谈的结果进行定性的内容分析。 结果 两个城市提供避孕服务的质量上并没有差异，都没有满足十项质控标准的半数以上。总结访谈内容发现四个与避孕服务质量相关的主题：避孕服务的指导方针以及实用的电子表格；好的避孕咨询的标准，避孕方法的可获得性以及性健康。访谈中发现Norröping的相关领导的工作存在不足，相关信息缺乏以及没有为提供避孕服务的人员安排持续的培训以及与妇科医生的交流来保证知识的更新。 结论 两个城市的计划生育诊所提供的避孕服务质量相同，造成他们流产率差异的原因并非在此，具体的原因还尚待进一步确定